Box-Behnken Design Optimization Process of Electrospinning for Fabrication PLA/PVA Nanofibers - Yadi Mulyadi Rohman; Dendin Supriadi (CV. Get Press Indonesia, 2025)
The optimization of PLA/PVA nanofibers has been successfully performed using the Box-Behnken design method to produce nanofibers with small diameters. The fabrication process of the nanofibers was conducted using electrospinning. The electrospinning process parameters included PLA solution concentration, voltage, and flow rate. The optimal conditions for producing the nanofibers were found in sample N1, with variations of PLA solution at 9%, voltage at 14 kV, and flow rate at 16 kV, resulting in small and uniform nanofibers. The smallest fiber diameter achieved was 152.67 nm, which is quite close to the Box-Behnken predicted value of 144.45 nm. Statistical testing was conducted using analysis of variance (ANOVA), which indicated a p-value greater than 0.03 for the effect of the flow rate. This demonstrates that the flow rate has a significant influence on the diameter size. These results indicate that the Box-Behnken design can be an important tool for optimizing processes in electrospinning.